PERAN CUSTOMER SATISFACTION MEMEDIASI PENGARUH ONLINE TRUST TERHADAP REPURCHASE INTENTION (Studi pada Konsumen Florist Online di Kota Denpasar) - Devi, Putu Sonia Chandra; Sulistyawati, Eka (E-Jurnal Manajemen; Vol 7 No 6 (2018)DO - 10.24843/EJMUNUD.2018.v07.i06.p01, 2018)
This study determine the role of customer satisfaction inmediating influence online trust on repurchase intention to consumers online florist. The study was conducted in Denpasar, involving 100 respondents throughmethod. purposive samplingData were collected through questionnaires.Data analysis technique used is the technique of path analysis (pathanalysis) and Sobel test. The study found that online trust and a significant positive effect on repurchaseintention. Online trust positive and significant impact on customersatisfaction. Customer satisfaction and significant positive effect on repurchaseintention. customer satisfaction mediating influence Onlinetrust on repurchaseintention,which indicates that online trust accompanied by customer to influence and determine satisfaction,repurchase intention consumer online florist in Denpasar. Suggested formerchants online in increasing the intention to repurchase on the consumer, it is important formerchants, online especially online florist to further undermined trust and satisfaction of its customers. Keywords: online trust, customer satisfaction, repurchase intention.